Science teachers' perception on the termination of ETeMs / Rozita Muhammad - Muhammad, Rozita (2012)
The implementation of ETeMs in 2003 required the science teachers to have essential English proficiency in order to convey the science content effectively. Difficulties arose as the teachers were said to not have enough competence. This study which adopted the survey method, was designed to investigate the perception of science teachers in Marang district of Terengganu regarding the use of English in science teaching. It is also aimed at finding out their opinion regarding their students' achievement after the implementation of ETeMs. It is also to find out their opinion on the termination of ETeMs and the introduction of MBMMBL For this purpose fifty (50) respondents who were the primary schools teachers in Marang district were selected using the purposive sampling method. Two types of instrumentation were used in order to get the data for this study. They were a set of questionnaires and structured interviews. The data collected was analysed using SPSS and descriptive analysis of frequencies and percentages were conducted to get the findings. The findings revealed that most of the science teachers (68%) in Marang district agreed with the termination of ETeMs. The main reason for this was dissatisfaction among them regarding the use of English in the teaching of science. 56% of them did not enjoy teaching science in English and 52% stated that teaching science in English was a burden to them. They also agreed with the government's decision to introduce MBMMBI in order to enhance both English and Malay Language among the students. 72% of them were in favour of MBMMBL 88% belief that MBMMBI is able to enhance the students' English command while 90% of them agreed that MBMMBI is a good move to improve students' proficiency in both languages.